Longitudinal Mental Health Outcomes of Third-year Medical Students Rotating Through the Wards During COVID-19. (February 2023) - Stanislawski, Emma R.; Saali, Alexandra; Magill, Elizabeth B.; Deshpande, Richa; Kumar, Vedika; Chan, Chi; Hurtado, Alicia; Charney, Dennis S.; Ripp, Jonathan; Katz, Craig L.
Highlights: 74% of third year medical students screened positive for depression, anxiety, or PTSD. Prevalence of psychiatric symptoms highest in June 2020 for third year medical students. No differences in mental health outcomes over the academic year. Psychological distress, childhood abuse, resilience predicted mental health outcomes. COVID-19 worries and clerkship related events did not impact psychological well-being. Abstract: This study investigated third year medical students' psychological well-being during clinical rotations at Mount Sinai hospitals in New York City during the COVID-19 pandemic. All students ( n  = 147) starting rotations (psychiatry, surgery, obstetrics-gynecology, neurology, pediatrics, and medicine) could participate in quarterly, online, anonymous surveys comprised of validated screeners for: psychological symptoms, risk, coping, and protective factors, demographics, COVID-19 worries, and stressful clerkship-related events. Associations between variables were examined with Chi-squared, Fisher's exact, t-, Wilcoxon Rank Sum, one-way ANOVA, and McNemar tests. Significant univariate predictors of psychological distress were included in stepwise multivariable linear regression models. The baseline survey was completed by 110 (74.8%) students; ninety-two (62.6%) completed at least one other survey. During the year, 68 (73.9%) students screened positive for depression, anxiety, or PTSD. The prevalence of psychiatric symptoms peaked in June 2020 without significant changes in average scores over time. COVID-19 worries decreased over time but did not influence psychological symptoms at year-end. Eighty-three students (90.2%) experienced stressful clerkship-related events, which were traumatic and/or COVID-19-related for 26 (28.3%) and 22 students (24.0%), respectively. Baseline psychological distress, childhood emotional abuse, and resilience predicted depression, anxiety, and/or PTSD by year-end. This study highlights the importance of recognizing psychological distress and implementing interventions to support students' well-being.